Centralised versus decentralised treatment and disposal options for Küçükçekmece Basin of Istanbul City - Eroğlu, V.; Sarikaya, H Z.; Yüksel, E.; Koyuncu, I. (IWA Publishing, 2002)
Küçükçekmece Lake is a sea lagoon located on the European side of Istanbul city with a drainage area of 4 million inhabitants (year 2040). The original plan to treat all of the wastewater collected from the drainage basin in a single plant located at the Northern end of the lake is compared with the decentralised option involving 4 treatment plants. The initial investment cost of the decentralised option is estimated to be higher than the original plan by an amount of 43 million US $. However, the decentralised option has been chosen finally, considering the low cost and risk of wastewater collection, the possibility of the staging of the services, and the reduced environmental impacts.
Keywords: Turkey; Water Pollution; Costs and Cost Analysis; Cities; Risk Assessment; Waste Disposal, Fluid